Smooth approximation of bi-Lipschitz orientation-preserving homeomorphisms - Daneri, Sara; Pratelli, Aldo (Annales de l'Institut Henri Poincaré - Analyse Non Linéaire, 2014)
We show that a planar bi-Lipschitz orientation-preserving homeomorphism can be approximated in the W-1,W-P norm, together with its inverse, with an orientation-preserving homeomorphism which is piecewise affine or smooth. (c) 2013 Elsevier Masson SAS. All rights reserved.